Pengaruh Leverage, Efisiensi, Dan Ekonomi Makro Terhadap Kebijakan Deviden Perusahaan Listing Sri-Kehati Indeks - Kevin Bambang Setiawan; Andreas Fourtunando Simanjuntak; Putri Br Sibarani; Dwita Sakunta; Arsyaf Tampubolon (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze the factors that influence dividend policy, namely leverage, efficiency and macroeconomics in 20 companies that carry the green concept (SRI) listed on the Indonesia Stock Exchange for the 2017-2021 period. The sampling technique in this study was purposive sampling method and 100 samples were obtained. The analytical method used is multiple linear regression analysis. The results of this study indicate that efficiency has an effect on dividend policy, while leverage and macroeconomic factors have no effect on dividend policy. Keywords: Leverage, Efficiency, Macroeconomics and Dividend Policy